The Influence of Agricultural Facilities and Infrastructure on Farmer Behavior: A COM-B Study in Kondamara, Lewa Subdistrict: A COM-B Model Study in Kondamara Village, Lewa Subdistrict - Mariska Ratu Eda; Junaedin Wadu (BIOSAINSTEK, 2025)
This study investigates the influence of agricultural facilities and infrastructure on farmer behavior in managing lowland rice farming in Kondamara Village, Lewa Subdistrict, East Sumba Regency, using the COM-B model (Capability, Opportunity, Motivation–Behavior). A quantitative approach was employed through Structural Equation Modeling–Partial Least Squares (SEM-PLS), with data collected from 100 farmers via structured questionnaires and field observations. The results reveal that agricultural infrastructure—such as irrigation systems, farm roads, and farmer groups—has a significantly stronger impact (path coefficient = 0.766; f² = 2.292) on farmer behavior than mechanized facilities (path coefficient = 0.219; f² = 0.187). The model's high predictive accuracy is demonstrated by an R² value of 0.852. These findings underscore the strategic importance of developing agricultural infrastructure and empowering farmer groups as key interventions to foster adaptive and sustainable farming behavior, particularly in food-insecure rural areas.